2020
DOI: 10.12659/msm.920278
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Nuclear Receptor Subfamily 4 Group A Member 1 (Nr4a1) and Liver Linase B1 (LKB1) Mitigates Type 2 Diabetes Mellitus by Activating Monophosphate-Activated Protein Kinase (AMPK)/Sirtuin 1 (SIRT1) Axis and Inhibiting Nuclear Factor-kappa B (NF-κB) Activation

Abstract: Departmental sources Background: Nuclear receptor subfamily 4 group A member 1 (Nr4a1) has been increasingly investigated in association with type 2 diabetes mellitus (T2DM). This study aimed to explore its efficacy with liver kinase B1 (LKB1) and potential signaling pathways in T2DM. Material/Methods: A T2DM model in rats was established by high-fat diet and injection of 30 mg/kg streptozotocin. The ectopic expression of Nr4a1 or in combination with LKB1 was performed in T2DM rats to probe their effects on T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Neutrophil degranulation [52], innate immune system [53], platelet degranulation [54], extracellular matrix organization [55], diseases of glycosylation [56], platelet activation, signaling and aggregation [57], hemostasis [58], secretion [59], secretory vesicle [60], transmembrane transporter activity [61], cell adhesion [62], localization of cell [63], extracellular matrix [55], intrinsic component of plasma membrane [64], structural molecule activity [65], signaling receptor binding [66], have been highly noted in T2DM. Reports indicate that HIF1A [67], HLA-DRB1 [68], CHI3L1 [69], ADORA2A [70], ADRB2 [71], CLU (clusterin) [72], AGT (angiotensinogen) [73], VCAM1 [74], PPARA (peroxisome proliferator activated receptor alpha) [75], APOL1 [76], ZFP36 [77], PPM1B [78], SOCS1 [79], SNCA (synuclein alpha) [80], CTSS (cathepsin S) [81], IL6R [82], CFB (complement factor B) [83], DEFB1 [84], VNN1 [85], RAB27A [86], DPP4 [87], RARRES2 [88], CASP1 [89], LCN2 [90], REG3A [91], CD74 [92], PCSK2 [93], CHGB (chromogranin B) [94], TTR (transthyretin) [95], LRG1 [96], ALB (albumin) [97], DPP7 [98], APOH (apolipoprotein H) [99], CTSD (cathepsin D) [100], GCG (glucagon) [101], KCNQ1 [102], NR4A1 [103], PLIN5 [104], ALDH2 [105], ANG (angiogenin) [106], CLDN7 [107], PRLR (prolactin receptor) [108], SOD2 [109], MLXIPL (MLX interacting protein like) [110], CTSD (cathepsin D) [111], PECAM1 [112], ADA (adenosine deaminase) [113], MFGE8 [114], COL1A1 [115], COL3A1 [116], NID2 [117], ARG1 [118], CD93 [119], IGF2 […”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil degranulation [52], innate immune system [53], platelet degranulation [54], extracellular matrix organization [55], diseases of glycosylation [56], platelet activation, signaling and aggregation [57], hemostasis [58], secretion [59], secretory vesicle [60], transmembrane transporter activity [61], cell adhesion [62], localization of cell [63], extracellular matrix [55], intrinsic component of plasma membrane [64], structural molecule activity [65], signaling receptor binding [66], have been highly noted in T2DM. Reports indicate that HIF1A [67], HLA-DRB1 [68], CHI3L1 [69], ADORA2A [70], ADRB2 [71], CLU (clusterin) [72], AGT (angiotensinogen) [73], VCAM1 [74], PPARA (peroxisome proliferator activated receptor alpha) [75], APOL1 [76], ZFP36 [77], PPM1B [78], SOCS1 [79], SNCA (synuclein alpha) [80], CTSS (cathepsin S) [81], IL6R [82], CFB (complement factor B) [83], DEFB1 [84], VNN1 [85], RAB27A [86], DPP4 [87], RARRES2 [88], CASP1 [89], LCN2 [90], REG3A [91], CD74 [92], PCSK2 [93], CHGB (chromogranin B) [94], TTR (transthyretin) [95], LRG1 [96], ALB (albumin) [97], DPP7 [98], APOH (apolipoprotein H) [99], CTSD (cathepsin D) [100], GCG (glucagon) [101], KCNQ1 [102], NR4A1 [103], PLIN5 [104], ALDH2 [105], ANG (angiogenin) [106], CLDN7 [107], PRLR (prolactin receptor) [108], SOD2 [109], MLXIPL (MLX interacting protein like) [110], CTSD (cathepsin D) [111], PECAM1 [112], ADA (adenosine deaminase) [113], MFGE8 [114], COL1A1 [115], COL3A1 [116], NID2 [117], ARG1 [118], CD93 [119], IGF2 […”
Section: Discussionmentioning
confidence: 99%
“…Emmens et al [39] found that PENK (proenkephalin) expression was up regulated in cardiovascular diseases, but this gene might be responsible for progression of T2DM. Recent studies have proposed that the SAA1 [ [101], KCNQ1 [102], NR4A1 [103], PLIN5 [104], ALDH2 [105], ANG (angiogenin) [106], CLDN7 [107], PRLR (prolactin receptor) [108], SOD2 [109], MLXIPL (MLX interacting protein like) [110], CTSD (cathepsin D) [111], PECAM1 [112], ADA (adenosine deaminase) [113], MFGE8 [114], COL1A1 [115], COL3A1 [116], NID2 [117], ARG1 [118], CD93 [119], IGF2 [120], IL18 [121], LAMA1 [122], HPSE (heparanase) [123], BMP4 [124], CXCR4 [125], KDR (kinase insert domain receptor) [126], ESAM (endothelial cell adhesion molecule) [127], THBS1 [128], CD34 [129], SERPINE1 [130], WNT5B [131], MGP (matrix Gla protein) [132], MMP3 [133], MMP9 [134], MMP11 [135], IL16 [136], TNFRSF11B [137], TIMP3 [138] and CAPN3 [139] were found in T2DM. HLA-A [140], HLA-B [141], HLA-C [142], HLA-DPB1 [143], HLA-E [144], ERBB3 [145], MFAP4 [146] and JAK3…”
Section: Discussionmentioning
confidence: 99%
“…As a secondary and long-term effect, AMPK phosphorylates TFs SREBP1c and ChREBP, thus inhibiting the transcription of subsequent lipogenic genes [65]. Sirtuin proteins (SIRT1 and SIRT3) stimulate AMPK via deacetylation of its upstream activator LKB1 (liver kinase B1) [66]. Nowadays, sirtuins are recognised as crucial regulators of lipid metabolism, providing tissue-specific FAO-promoting activities (in skeletal muscle and liver), lipolysis (in adipose tissue), mitochondrial respiration (BAT (brown adipose tissue)), and food intake (in the hypothalamus) [67].…”
Section: Figurementioning
confidence: 99%
“…Otro probable mecanismo, es a través de la sirtuina-1 (SIRT1), proteína implicada en procesos de antienvejecimiento y antiinflamatorio, evidenciando una restricción calórica durante su activación (Penumetcha & Santanam 2012). La SIRT-1 dependiente de la deacetilación del PPARg ha demostrado una forma de modulación selectiva en este receptor, permitiendo la inducción de los genes BAT (tejido adiposo marrón) y supresión de los genes WAT (tejido adiposo blanco) viscerales, asociados con la resistencia a insulina (Qiang et al 2012;Ming et al 2020). Asimismo, flavonoides como quercetina, tienen efecto hipoglucemiante sobre la alfa-glucosidasa favoreciendo la fosforilación de la glucosa, para formar glucosa 6-fosfato, paso limitante para la glucólisis y regulación de la glicemia (Karato et al 2006 2015), prueba de ello es que se evidencia reportes discordantes de su actividad antibacteriana, incluso tratándose de la misma especie vegetal (Tabla 4).…”
Section: Etnofarmacologíaunclassified